Weather index insurance for managing drought risk in smallholder agriculture: lessons and policy implications for sub-Saharan Africa - Million A. Tadesse; Bekele A. Shiferaw; Olaf Erenstein (Agricultural and Food Economics, 2015)
This paper reviews recent advances in, and challenges for, weather index insurance for managing drought risk in smallholder agriculture, with a focus on sub-Saharan Africa. Despite its promise to integrate local agricultural risk smoothing with insurance principles, there remain many challenges to its mainstreaming in low income countries. Scaling up of weather index insurance pilot projects is particularly constrained by high-basis risk, related to the divergence between the calculated weather index and actual productivity loss on the farm. Various options may be considered to enhance uptake of weather index insurance. Linking reliable weather data with location-specific crop and agronomic conditions using flexible geospatial crop modeling tools is one option to reduce the basis risk. The other option is interlinking weather index insurance with credit or safety nets. In the end, insurance should be offered as part of a wider set of business services that provide real value to smallholders. Finally, the review acknowledges that the suggested conceptual solutions, especially interlinking index based weather insurance with credit will require more empirical evidence on the extent to which insurance would reduce the cost of borrowing and make credit more accessible to the smallholder farmers.
Keywords: 330; Index-based weather insurance; Inter-linkage; Credit; Safety net; Sub-Saharan Africa